Analisis Kesalahan Mahasiswa Pendidikan Matematika Stambuk 2021 Universitas Negeri Medan dalam Menyelesaikan Soal Grup Permutasi - SL Manurung; Chindy Fransiska Hutagalung; Fiqri Subhan; Naila Ghinaya Damanik; Sofi Fatinah (Journal on Education, 2024)
The purpose of this study was to identify student errors in solving Permutation problems. This research is a qualitative descriptive research. The subjects of the study were 4 6th semester students of the Mathematics Education study program at Medan State University. Data collection is done by providing problems or problems. Data is analyzed through the stages of data reduction, data presentation and conclusions. The results showed that the difficulty of learning mathematics in college was caused by weak mastery of aspects of complicated and complex mathematical concepts. Drawing these conclusions is important as an answer to the research question